The Effect of Organizational Citizenship Behavior (OCB) on Counterproductive Work Behavior: The Mediating Role of Citizenship Fatigue and Burnout and The Moderating Role of Perceived Organizational Support (POS) among Healthcare Workers - Indy Asna Azizah; Zuyyina Choirunnisa (Journal Research of Social Science, Economics, and Management, 2026)
Healthcare workers, particularly nurses, are required to maintain high professionalism, rapid response, and patient safety, yet excessive work demands may trigger psychological fatigue and counterproductive work behavior. This study aimed to analyze the effect of Organizational Citizenship Behavior (OCB) on Counterproductive Work Behavior (CWB) through the mediating roles of citizenship fatigue and burnout, as well as the moderating role of Perceived Organizational Support (POS) among healthcare workers in Jombang Regency. This research employed a quantitative explanatory approach involving nurses working in hospitals, health centers, and clinics. Respondents were selected using purposive sampling, with criteria including active nurses with at least one year of work experience and direct involvement in health services. Data were collected through an online Likert-scale questionnaire and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS. The results showed that OCB significantly increased citizenship fatigue, while citizenship fatigue significantly increased burnout and CWB. Burnout also had a significant positive effect on CWB. However, OCB directly reduced CWB, indicating its dual role. POS significantly weakened the relationship between OCB and citizenship fatigue but did not moderate the relationship between OCB and burnout. In conclusion, excessive OCB may create psychological costs, but organizational support can reduce its negative effects.